2021
DOI: 10.13189/ujaf.2021.090212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 News on Performance of Indonesia Stock Market

Abstract: This research tries to show that information about COVID-19 affects market arousal indicated by the frequency of transactions, and the market performance shown by Jakarta Composite Index (JCI). The theory used for analysis is the prospect theory and efficient market hypothesis (EMH). The results of statistical analysis indicate that information about COVID has a negative effect on JCI, as well as trading volume the previous day. The evidence can briefly prove that there is an effect of COVID-19 and weakening d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…The implementation of the measures presented in Figure 2 will help to create the institutional and legal prerequisites for the reliable financial security of the monetary sector. But, without improving the institutional and economic mechanism of monetary policy to ensure the financial security of the state, it is impossible to achieve balance and coherence among all subjects and regulators of this process [18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The implementation of the measures presented in Figure 2 will help to create the institutional and legal prerequisites for the reliable financial security of the monetary sector. But, without improving the institutional and economic mechanism of monetary policy to ensure the financial security of the state, it is impossible to achieve balance and coherence among all subjects and regulators of this process [18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The presentday investors strongly believe that investment in the stock market doesn't go futile and results in getting an attractive reward in comparison to the other investment avenues. According to the efficient market hypothesis, investors' decision-making behavior is aggregated in market dynamics and is subsequently manifested in share price and index fluctuations (Haryanto & Mawardi, 2021) [11]. It is important to monitor the stock price movement because it's a key factor that impedes the stock market and consumer spending.…”
Section: Scholarly Review Of Research Literaturementioning
confidence: 99%
“…Sharma et al [22] also examined the data of the fifteen most affected countries from February 1 to May 13, 2020 and showed that after control of other factors, there was a strong relationship between infection cases and stock returns. Haryanto and Mawardi [16] found out the significant impact of COVID-19 news on the performance of Indonesia stock market.…”
Section: Review Of Literaturementioning
confidence: 99%